2022
DOI: 10.1097/bor.0000000000000922
|View full text |Cite
|
Sign up to set email alerts
|

An update on autoantibodies in systemic lupus erythematosus

Abstract: Purpose of reviewAutoantibodies are cornerstone biomarkers in systemic lupus erythematosus (SLE), an autoimmune disease characterized by autoantibody-mediated tissue damage. Autoantibodies can inform about disease susceptibility, clinical course, outcomes and the cause of SLE. Identifying pathogenic autoantibodies in SLE, however, remains a significant challenge. This review summarizes recent advances in the field of autoantibodies in SLE.Recent findingsHigh-throughput technologies and innovative hypothesis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In contrast to other autoimmune kidney diseases that are restricted to a specific autoAb (e.g., anti-collagen IV Abs in glomerular basement membrane), a vast array of autoAbs characterize LN patients with distinct subsets present in the kidney [58]. Indeed, the pioneering experiment conducted by Mannik et al from 23 post-mortem kidneys revealed the presence of a large panel of polyreactive Abs targeting dsDNA/chromatin/histone, Sm/RNP, SSA/B, C1q, and phospholipids [59].…”
Section: Nephropathic Antibodies In Lnmentioning
confidence: 98%
“…In contrast to other autoimmune kidney diseases that are restricted to a specific autoAb (e.g., anti-collagen IV Abs in glomerular basement membrane), a vast array of autoAbs characterize LN patients with distinct subsets present in the kidney [58]. Indeed, the pioneering experiment conducted by Mannik et al from 23 post-mortem kidneys revealed the presence of a large panel of polyreactive Abs targeting dsDNA/chromatin/histone, Sm/RNP, SSA/B, C1q, and phospholipids [59].…”
Section: Nephropathic Antibodies In Lnmentioning
confidence: 98%
“…Autoantibodies circulating in body fluids or forming immune complexes in peripheral tissues have been used as valuable diagnostic and prognostic biomarkers in SLE for predicting pathogenic pathways and for guiding therapeutic treatments [ 123 , 124 ]. Therefore, in recent years, several efforts have been made to improve the detection of autoantibodies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…We think that in addition to anti-C1q, anti-dsDNA, anti-Smith (anti-Sm), anti-Ro/SSA, anti-La/SSB, anti-ribonucleoprotein (anti-RNP), anti-phospholipid antibodies, and complement fractions should be included in the panel of autoantibodies that any patients with suspected of LN should tested at baseline. Recently, anti-alfa enolase (ENO1), anti-histone 2 IgG2, antibodies directed against superoxide dismutase 2 (SOD2), anti-chromatin, anti-nucleosome and ribosomal P emerged in experimental studies, as possible biomarkers of active lupus nephritis, but are not yet available in the clinical setting ( 58 , 59 , 63 ). Considering the healthcare expenditure of testing the entire panel of available antibodies, complete screening should be performed at SLE diagnosis, while only anti-dsDNA, anti-C1q, and complement fractions should be tested to monitor LN during follow-up.…”
Section: Anti-c1q In Lupus Nephritismentioning
confidence: 99%